ChemInform Abstract: A Novel and Convenient Method for the Synthesis of New Derivatives of Pyrido[3, 2‐e]pyrrolo[1, 2‐a][1, 4]diazepine‐6, 11‐dione. Issue 13 (18th March 2013) - El Bouakher, Abderrahman; Prie, Gildas; Aadil, Mina; Lazar, Said; Akssira, Mohamed; Viaud‐Massuard, Marie‐Claude
Abstract A novel and efficient access to new optically active 2‐substituted pyridopyrrolodiazepine derivatives is developed involving peptide coupling of 3‐aminopyridinecarboxylic acid (I) with proline ester [→(III)] and intramolecular cyclization of corresponding brominated coupling product (IV) as the key steps.